3D Co3O4‐RuO2 Hollow Spheres with Abundant Interfaces as Advanced Trifunctional Electrocatalyst for Water‐Splitting and Flexible Zn–Air Battery. (12th July 2022) - Gao, Yuxiao; Zheng, Debo; Li, Qichang; Xiao, Weiping; Ma, Tianyi; Fu, Yunlei; Wu, Zexing; Wang, Lei
Abstract: Exploiting efficient and stable electrocatalysts with trifunctional catalytic activity toward hydrogen evolution reaction (HER), oxygen evolution reaction (OER), and oxygen reduction reaction (ORR) act has a crucial role with sustainable energy development. Therefore, this study fabricates Co3 O4 ‐RuO2 hollow spheres using a facile and eco‐friendly solvothermal and low temperature oxidation procedure followed by ice water treatment (IW‐Co3 O4 ‐RuO2 ‐HS). The specific hollow nanostructure could provide sufficient active sites and channels in the electrocatalytic procedure. Then, the IW‐Co3 O4 ‐RuO2 ‐HS presents small overpotentials toward HER (40 mV@ 10 mA cm −2 ) and OER (250 mV@ 10 mA cm −2 ), and high half‐wave potential for ORR (E1/2 @ 0.79 V). Remarkably, the IW‐Co3 O4 ‐RuO2 ‐HS also presents superior catalytic performances toward water‐splitting and flexible rechargeable Zn–air batteries. Furthermore, the water electrolysis can be driven by sustainable energy, including solar, wind, thermal energy, and the assembled flexible rechargeable Zn–air battery. This study provides a valid path to synthesize multifunctional electrocatalysts on energy‐related devices. Abstract : The IW‐Co3 O4 ‐RuO2 ‐HS is prepared via a facile and simple solvothermal followed by a low‐temperature oxidation process. The obtained nanomaterials exhibit excellent electrocatalytic performances for overall water‐splitting and flexible rechargeable Zn–air batteries.